Peran Ekonomi Kreatif terhadap Penyerapan Tenaga Kerja dan Peningkatan Pendapatan Pelaku Industri Kreatif Dalam Perspektif Ekonomi Islam di Kota Medan - Rafika Azwina; Atika Atika; Budi Dharma (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to determine how the influence of the creative economy on employment and the increase in income of creative industry actors is perceived from the perspective of Islamic economics in the city of Medan by using descriptive qualitative. This study uses primary data from in-depth interviews with 20 creative industry business owners in the city of Medan. The creative economy sub-sector has a major contribution to the national economy, namely 7.44% of the Gross Domestic Product (GDP), 14.28% of the workforce and 13.77% of exports. The results of this study indicate that the craft sector is the sector that absorbs the most labor and the creative economy can increase the income of creative industry players. The management of creative industry businesses is in accordance with an Islamic economic perspective because they not only seek profit but also carry out their spiritual aspects and provide benefits to consumers and no one feels disadvantaged. Keywords: Creative Economy, Workforce, Income.